Electrochemical oxidation of amoxicillin on carbon nanotubes and carbon nanotube supported metal modified electrodes - Ferreira, Marta (2020)
Supplementary material related to this article can be found, in the online version, at doi:https://doi.org/10.1016/j.cattod.2019.06.039.